Biodegradation of toluene by a lab-scale biofilter inoculated with Pseudomonas putida DK-1 - Park, D W (Environmental technology, 2002)
The biodegradation of toluene by biofiltration inoculated with Pseudomonas putida DK-1 was investigated with variation of the several environmental parameters, such as temperature, bed length, gas flow rate and optimal humidity zone. The optimal temperature range to treat toluene gas was found to be 32-35 degrees C. Increasing the gas flow rate showed an inverse effect on the elimination capacity and the removal efficiency. The optimal gas flow rate was obtained at 65 ml min(-1) from the relation between the removal efficiency and the elimination capacity. The biodegradation rate of the toluene with respect to the bed lengths (3, 6, 9, 12 and 15 cm) increased up to 80 h but was then independent of the bed lengths after 80 h except for the 3 cm bed length. The elimination capacity was improved by about 70% compared with that reported in other literature and was also in agreement with theoretical models